Numerical computation of incoherent bremsstrahlung from fast electrons in single crystals - Shul’ga, N.F.; Syshchenko, V.V.; Tarnovsky, A.I. (Вопросы атомной науки и техники, 2009)
The incoherent bremsstrahlung of fast electrons in crystal is caused by thermal spread of atoms from their equilibrium positions in the lattice. Its intensity manifests substantial orientation dependence under angles of incidence close to critical angle of planar or axial channeling. The simulation procedure for the incoherent radiation is developed. The results of simulation are in a good agreement with the experimental data.